Pengaruh Discount Promo dan Customer Experience Terhadap Customer Loyalty (Studi pada Mahasiswa Kota Medan Pengguna Grab) - Sherina Alim; Nana Dyki Dirbawanto (Politeknik Kampar, 2024)
The advent of information technology has precipitated substantial shifts in the manner by which humans interact and conduct transactions, particularly in the context of online transportation services such as Grab. Despite Grab's commendable user experience rating, it remains less popular than Gojek. This study aims to investigate the influence of discount promotions and customer experience on customer loyalty among university students who use Grab in Medan City. This study employs a quantitative approach with an associative method. The research sample consisted of 96 respondents selected through purposive sampling from the student population of Grab users in Medan City. Primary data were obtained through direct questionnaire distribution, while secondary data were collected through a literature review. Data analysis was conducted using SPSS version 26 software, which included validity tests, reliability tests, classical assumption tests, multiple linear regression, as well as partial, simultaneous, and determination tests. The results demonstrated that a discount promotion has a notable positive impact on customer loyalty, as indicated by a t-count value of 1.995, a sig value of 0.049, and a regression coefficient of 0.176. Additionally, customer experience was found to have a significant positive effect on customer loyalty, with a t-count value of 8,021 and a sig value of 0.000, and a regression coefficient of 0.735. The simultaneous testing demonstrates that discount promotions and customer experience collectively account for 76.2% of customer loyalty, while 23.8% is attributed to other factors not included in this study. This research offers significant insights into the factors influencing customer loyalty in the context of online transportation services.